POLEMIK PRAKTIK SAWERAN KEPADA PEMBACA AL-QUR’AN (Telaah Etika Interaksi dengan al-Qur’an) - Desri Ari Enghariano (Institut Agama Islam Negeri Padangsidimpuan, 2023)
Al-Qur’an is a holy book that is very sacred for a muslim person. They are commanded to read, study, understand, and venerate it. However, the sacredness of the Qur’an has been tarnished recently by the uncivilized behavior of some muslims. One of the actions that contaminates the sacredness of the Qur’an and insults its glory is an action called saweran to the reader of the Qur’an. The practice of saweran is very concerning, because it has become a tradition or culture in several regions. There is no longer any difference between singer and expert ont the Qur’an. Therefore, research and study of ethics to the Qur’an and Qur’an experts are still relevant and urgent to study.This research is library research, namely research using written materials, such as books, journals, magazines, and so on. This research is a qualitative research of interpretation and presentation of data by means of descriptive-analytic method. Thematic method is the choice in completing this research. The results of this research indicate that muslims should leran more about the ethics of interaction with the Qur’an and Qur’an experts. Reading the Qur’an begins with brushing your teeth and reciting it solemnly. The experts of the Qur’an must be glorified and respected. Al-Qur’an teachers must be sincere in their intentions, gentle with their students, and enthusiastic. Al-Qur’an students must be study with the right teacher, respect their teacher, and be enthusiastic. The memorizes of the Qur’an must guard againts disgraceful occupations, have a noble soul, not be greedy for worldly possessions, and not joke too much.